EKO-EPIDEMIOLOGI PENULARAN MALARIA DI DAERAH ENDEMIS PULAU LEMUKUTAN KALIMANTAN BARAT - Selviana; Pranaka, Resky Nanda; Rahayu, Hanum Mukti (JURNAL BORNEO AKCAYA, 2015)
Lemukutan island is on area of endemic malaria with the High Incidence Area status. Every year there was an increase of Annual Parasite Incidence (API). Lemukutan is isolated, where the environment and people's homes are surrounded by oceans, and their place is behind the plantation area. The purpose of this research is to get the information about ec0-epidemiology transmission of malaria in endemic area Lemukutan Island bengkayang regency. Cross sectional design is used in this research methodology, which is held on April – June 2015. Sample is 170 respondents. The analysis is univariate and bivariate. The result showed that significant determinant of malaria occurrence are behavior (p value = 0,036, PR = 1,726), ventilation (p value = 0,046, PR = 1,927), the ceiling (p value = 0,033, PR = 1,808), well/fountain around (p value = 0,004, PR = 2,523), bushes (p value = 0,008, PR = 2,221) dan cattle pen (p value = 0,04, PR = 1,746) with incidence in village of Lemukutan Island. There is no relationship between jobs and incidence in village of Lemukutan Island (p value = 0,537, PR = 1,746). Researcher give the suggestion to society so that they can taking heed at the nip density time, using the long arm clothes and anti mosquito lotion, apply biological control that is by conducting bacteria Mysocyclops, mosquito larva eater fish and put down the resting places not closed to house